Environmental Survey and Photographic Documentation of a Forest Edge Hamlet Situated in Buxa Tiger Reserve, India - Bhattacharya, Sayan (European Scientific Journal, ESJ, 2017)
Buxa Tiger Reserve (BTR) is situated in Alipurduar district of West Bengal, India and is considered as one of the significant tiger reserves of India. The Reserve lies between Latitudes 23 o 30′ N to 23o 50′ N and Longitudes 89o 25′ E to 89 o 55′ E. It has 37 forest villages and 4 fixed demand holdings, 46 revenue villages and 34 tea gardens in and around it. The survey work was done in May, 2015 by visiting a forest edge village (Bhutia Basti) on the banks of Jayanti River in Buxa Tiger Reserve. It is the only village that has ever been relocated from the core area of Buxa Tiger Reserve. The position of the village is ecologically crucial as it is situated near the elephant corridors of Buxa. Primary data were gathered through field survey and direct contact with common people and authorized centres of the region. Structured and semi-structured questionnaire was administered in the village area. Surveys on the demography, agriculture, livestock management, water management, education, culture, health, waste management, disaster management, transport, biodiversity, joint forest management activities, Non-timber forest product usage and human animal conflict were done in this area. Human animal conflicts were studied in Bhutia Basti, as the village is periodically disturbed by the encroachment of elephant, rhinoceros and leopard. Biodiversity of the forest was documented by visiting the adjacent forest areas. Photographs were taken, analysed and interpreted in light of the survey data collected from the study area. There is an urgent need for implementing an integrated sustainable development system for the conservation of forest ecosystems and traditional human settlements in BTR.